TINJAUAN KRIMINOLOGI TERHADAP JURU PARKIR ILEGAL DI KAWASAN BEBAS BIAYA PARKIR DI KOTA PONTIANAK - NIM. A1011201234, MUHAMMAD ROY RAYHAN AGUS RIANTO (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractFree parking is one of the public facilities provided by the government or private sector to meet the needs of the public or vehicle users. This facility is very important, especially for those who have vehicles and need a safe and secure parking space. However, it often happens that there is a parking lot that has a banner or sign that says